The effect of ozonated sterile saline irrigation on the endometrium – A preliminary study. (3rd July 2016) - Calderon, Ilan; Cohen, Max; Sagi-Dain, Lena; Artzi, Ofir; Bejar, Jacob; Sagi, Shlomi
Abstract : The objective of this study was to evaluate the effect of sterile ozonated saline endometrial irrigation on sonographic and histological endometrial parameters. This prospective investigation was performed in 12 healthy, ovulating women over three consecutive menstrual cycles: control cycle (endometrial irrigation with 10 cc of normal saline at day 10), no intervention cycle and study cycle (irrigation with 10 cc of sterile ozonated saline at day 10). Endometrial thickness was measured by transvaginal ultrasound at days 10 and 12 of the control and study cycles, and endometrial samplings were obtained from the participants two days after the irrigations (i.e. on day 12) for histological evaluation. Ozonated saline irrigation, compared to normal saline irrigation, resulted in a statistically significant elevation of the columnar epithelial height (30.30 ± 3.04 vs. 25.82 ± 3.28 μm, p  < 0.003), increased number of endometrial blood vessels (30.48 ± 11.38 vs. 19.12 ± 8.74, p  < 0.005) and increased number of stromal cells (191.30 ± 34.40 vs. 151.29 ± 29.98, p  < 0.01). In conclusion, sterile ozonated saline irrigation of the endometrium has a significant favourable effect on various histological endometrial parameters. Further studies are needed to evaluate the effect of these changes on endometrial receptivity and pregnancy rates.